Neural mechanisms for learning self and other ownership. Issue 1 (December 2018) - Lockwood, Patricia; Wittmann, Marco; Apps, Matthew; Klein-Flügge, Miriam C.; Crockett, Molly; Humphreys, Glyn; Rushworth, Matthew
Abstract Sense of ownership is a ubiquitous and fundamental aspect of human cognition. Here we used model-based functional magnetic resonance imaging and a novel minimal ownership paradigm to probe the behavioural and neural mechanisms underpinning ownership acquisition for ourselves, friends and strangers. We find a self-ownership bias at multiple levels of behaviour from initial preferences to reaction times and computational learning rates. Ventromedial prefrontal cortex (vmPFC) and anterior cingulate sulcus (ACCs) responded more to self vs. stranger associations, but despite a pervasive neural bias to track self-ownership, no brain area tracked self-ownership exclusively. However, ACC gyrus (ACCg) specifically coded ownership prediction errors for strangers and ownership associative strength for friends and strangers but not for self. Core neural mechanisms for associative learning are biased to learn in reference to self but also engaged when learning in reference to others. In contrast, ACC gyrus exhibits specialization for learning about others. The sense of ownership – of which objects belong to us and which to others - is an important part of our lives, but how the brain keeps track of ownership is poorly understood. Here, the authors show that specific brain areas are involved in ownership acquisition for the self, friends, and strangers.